Discovery, development, and future application of senolytics: theories and predictions - Wissler Gerdes, Erin O. (FEBS J, 2020)
Senescent cells accumulate with aging and at etiological sites of multiple diseases, including those accounting for most morbidity, mortality, and health costs. Senescent cells do not replicate, can release factors that cause tissue dysfunction, and yet remain viable. The discovery of senolytic drugs, agents that selectively eliminate senescent cells, created a new route for alleviating age‐related dysfunction and diseases. As anticipated for agents targeting fundamental aging mechanisms that are ‘root cause’ contributors to multiple disorders, potential applications of senolytics are protean. We review the discovery of senolytics, strategies for translation into clinical application, and promising early signals from clinical trials.